A feasible and promising approach for diesel engine fuelled with a blend of biodiesel and low-viscosity Cinnamon oil: A comprehensive analysis of performance, combustion, and exergy. (15th May 2023) - Hoang, Anh Tuan; Balasubramanian, Dhinesh; Venugopal, Inbanaathan Papla; Rajendran, Vigneswaran; Nguyen, Dinh Tuyen; Lawrence, Krupakaran Radhakrishnan; Nguyen, Xuan Phuong; Kalam, M.A.
Abstract: Low viscous biofuel is one of the alternative sources in the recent past. The focus of this exploration is to assess the engine attributes with low viscous biofuel and to provide a feasible partial substitute with affordable power and reduced emissions. Indeed, Cinnamon oil was extracted from the bark of the Cinnamon tree using the steam distillation technique, and its physicochemical properties were probed as per the ASTM standards. The functional groups and fatty acid composition for the raw and extracted fuel samples were studied using FT-IR and GC-MS analysis. Later, low viscous Cinnamon oil was blended with high viscous Jatropha oil methyl ester (JOME) in the ranges of 70%, 80%, and 90% to form J30C70, J20C80 & J10C90 blends. Without any manual changes, the experiments were conducted on a single-cylinder diesel engine fuelled with J100 (100% JOME) and Cinnamon-blended JOME samples, and the outputs were compared with those of diesel fuel. As a result, the brake thermal efficiency of J10C90 was increased by 3.11% in comparison with J100. The emission such as CO, HC, and smoke were reduced by 26.02%, 28.16%, and 18.04% respectively compared with diesel fuel. From exergy analysis, the highest BTE of 28.91%, frictional loss of 6.47%, and mixing loss of 4.31% have been obtained for the J10C90 sample fuel. Finally, J10C90 is considered an optimum blended binary fuel for the upcoming future without the need for any substantial engine modifications. Highlights: Low-viscosity Cinnamon oil was a new viable additive fuel to mix with biodiesel. Cinnamon oil and Jatropha biodiesel were synthesized and used for all tests. Blend of 90% Cinnamon oil/10% Jatropha biodiesel (J10C90) was the best fuel sample. Higher BTE and much lower CO/HC/smoke than diesel fuel can be obtained for J10C90. Combustion and exergy analysis for J10C90 is better than other fuel samples.